Comparison of Transamine and Vasopressin for Peri-Oprative Blood Loss in Patients Undergoing Myomectomy: A Prospective Analysis - Fayyaz , Naima; Sajjad , Rabia; Naqvi , Sadiqa Batool; Hameed , M. Talha; Fayyaz , Amber; Nawaz , Qudsia (Indus Journal of Bioscience Research, 2025)
Background: Significant perioperative blood loss is frequently linked to myomectomy, a surgical operation used to remove uterine fibroids. This can result in consequences such anemia, hemodynamic instability, and the requirement for blood transfusions. Common hemostatic medications used to reduce blood loss include tranexamic acid (TXA) and vasopressin. Research on their relative efficacy in myomectomy is still ongoing, nevertheless. Objective: The purpose of this study is to evaluate how well Vasopressin and TXA reduce perioperative blood loss in patients having myomectomy. Hemodynamic stability, transfusion needs, intraoperative blood loss, and postoperative recovery results are all assessed in this study. Methodology: At Combined Military Hospital Lahore, 200 patients undergoing myomectomy participated in a prospective study. Patients were split into two groups, each with 100 participants: Group A (TXA) and Group B (Vasopressin). We gathered and examined information on hemodynamic stability, postoperative recovery, intraoperative blood loss, and transfusion requirements. Results: Compared to TXA (400 ± 50 mL), vasopressin showed a marginally higher reduction in intraoperative blood loss (350 ± 45 mL). Compared to the TXA group (12%), fewer patients (8%) in the Vasopressin group suffered from severe blood loss (>500 mL). Compared to the TXA group (15%), the Vasopressin group (10%) required fewer blood transfusions. Vasopressin also led to reduced postoperative hemoglobin decreases, shorter hospital stays (3 ± 1 days vs. 3.5 ± 1 days), and improved hemodynamic stability. Vasopressin, however, has been linked to certain cardiovascular hazards such arrhythmias and hypotensive episodes. Conclusion: Vasopressin and TXA both work well to reduce perioperative blood loss after myomectomy. Vasopressin showed excellent hemostatic control, which improved recovery results and decreased blood loss and transfusion requirements. However, cautious patient selection is required due to its cardiovascular adverse effects. TXA is still a safer option, especially for people who are at risk for cardiovascular disease. In order to improve blood management techniques in gynecological surgery, more extensive research is required.